2015
DOI: 10.1016/j.adolescence.2015.05.011
|View full text |Cite|
|
Sign up to set email alerts
|

Recurrence of suicide attempt in adolescents lost to contact early by clinicians: The 10‐year REPEATERS cohort of French adolescents

Abstract: Losing contact with adult suicide attempters in the year after the suicide attempt (SA) increases the risk of recurrence. The situation with adolescents is unknown. We aimed to determine whether being lost to contact early (LCE) by clinicians is a risk factor of long‐term SA recurrence among adolescents and the associated factors. Data were collected 10 years after an index SA and a Cox model was used for analysis. Among the 249 SA patients included, 59 (24%) were LCE, the most important risk factor of SA recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…Second, the data were collected in a single center where the adolescents who were on the psychiatric follow-up could be hospitalized more readily, regardless of their severity. Third, we did not include long-term outcomes as in several previous studies 6,11,12) . This study identifies predictors of the meaningful SAs, including the index methods and multiple SAs, in adolescents who visited the ED.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the data were collected in a single center where the adolescents who were on the psychiatric follow-up could be hospitalized more readily, regardless of their severity. Third, we did not include long-term outcomes as in several previous studies 6,11,12) . This study identifies predictors of the meaningful SAs, including the index methods and multiple SAs, in adolescents who visited the ED.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 69 (30.4%) patients connected with the social care service team (of 227 patients total), only 21(30.4%) agreed to follow ups, and only 11 completed case management a total of four times or reconnected to other social care service teams, while others refused or could not participate in postaccident care. Several studies have reported that the mortality and recurrence rate of suicide signi cantly decreased in patients who underwent follow-up care compared with those who did not [17,20]. Thus, because the prospective study design does not include long term output, mortality would increase.…”
Section: Discussionmentioning
confidence: 99%
“…This situation of suicidal attempts among adolescents includes limitations of available methods and higher impulsive tendencies, which differ from suicide attempts among adults [6, [10][11][12]. Thus, many studies exist on predictive factors for suicide attempts in young patients that distinguish them from those of adults; previous suicide attempts are one of the speci c predictive factors [6,10,[13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Et lorsque les adolescents établissent un premier contact avec le système soignant, l'alliance reste fragile. Dans une étude publiée par Ligier et coll., près d'un tiers d'un échantillon de 249 adolescents hospitalisés pour tentative de suicide n'a pas débuté le suivi proposé, et seuls 22 % poursuivaient un suivi à 6 mois [13].…”
Section: Discussionunclassified